Implementation of Blockchain Technology as the Latest Solution to Improve Data Security and Integrity - Dwi Yuda, M. Adhit; Watini, Sri (International Transactions on Education Technology (ITEE), 2023)
Blockchain technology represents an innovative solution for enhancing data security across various sectors. This research aims to examine the potential and challenges of blockchain technology in data security. The methodology employed involves a comprehensive literature review of up-to-date and relevant sources discussing the concepts, characteristics, types, and applications of blockchain technology, as well as the data security aspects associated with it. The findings of this study reveal that blockchain technology offers several advantages in data security, such as transparency, decentralization, immutability, and cryptography. However, it also confronts several obstacles, including scalability, interoperability, privacy, and regulatory concerns. This research offers recommendations and implications for addressing these challenges, such as the development of appropriate protocols and standards, fostering collaboration among stakeholders, and raising public awareness about the benefits and risks of blockchain technology. It is anticipated that this research will contribute to the development and future implementation of blockchain technology in data security